THE IMPACT OF CONTINUOUS MONITORING ON THE MENTAL WELL-BEING OF ELDERLY PATIENTS: A COMPREHENSIVE REVIEW OF PORTABLE DEVICES AND THEIR ROLE IN ENHANCING GERIATRIC CARE - Alves, Maria Laura de Biasi; Maronese, Francesco; Moraes, Daniella Gomes Rodrigues de; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
This narrative review explores the impact of continuous monitoring devices on the mental well-being of elderly patients. As the global population ages, there is an increasing need for innovative solutions to support the health and independence of older adults. Portable and continuous monitoring devices have emerged as promising tools for enhancing geriatric care, offering benefits such as early detection of health issues, improved management of chronic conditions, and support for independent living. However, the effects of these devices on the mental well-being of elderly patients remain understudied. This review synthesizes the current literature on the topic, discussing the potential benefits and challenges associated with continuous monitoring in the context of mental health. By examining the evidence through the lenses of clinical outcomes, patient experiences, and ethical considerations, this review provides a comprehensive understanding of the role of continuous monitoring in promoting the mental well-being of elderly patients. The findings highlight the need for further research and the development of guidelines to ensure these devices' effective and ethical implementation in geriatric care.